Emotional Intelligence Educational Card Game to Prevent Verbal Abuse at Elementary Schools in Southeast Pontianak - Nur Kur'ani; Rini Elvri (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Cases of verbal abuse in schools are often considered normal. For example, rude words to friends, such as saying “anjay" or making fun of parents' names, are considered part of student socialization. This study aims to find out the level of knowledge, attitudes, and behaviors of students about verbal abuse and how the educational card media affects verbal abuse behavior in schools. This study uses a quantitative approach with a quasi-experiment design and a pre-test and post-test model with a control group. Samples were taken from 16 students at State Elementary School 31 Pontianak Tenggara, comprising an experimental group of 8 students and a control group of 8 students. The results of the study were analyzed using the paired-samples t-test. The results of the study showed that after being given a knowledge-card media educational game, students' attitudes and behaviors improved, including reduced abusive language toward fellow students. The novelty of this study lies in the use of educational card media specifically designed as an intervention to increase students' awareness of the importance of positive communication at the elementary school level. This approach not only applies moral education theoretically but also uses interactive games to encourage direct changes in student behavior Keywords: verbal abuse behavior, educational card media, student behavior, educational games